1970
DOI: 10.3171/jns.1970.33.6.0689
|View full text |Cite
|
Sign up to set email alerts
|

Results of stimulation and destruction of the posterior hypothalamus in man

Abstract: Autonomic and somatomotor responses to electrical stimulation of the posterior hypothalamus are reported in 51 patients with pathologically aggressive behavior. The stimulated area causing rise in blood pressure, tachycardia, and maximal pupillary dilatation lies in the posteromedial hypothalamus, more than 1 mm and less than 5 mm lateral to the lateral wall of the third ventricle, occupying a triangle formed by the midpoint of the intercommissural line, the rostral end of the aqueduct, and the anterior border… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
0
12

Year Published

1973
1973
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(168 citation statements)
references
References 14 publications
(2 reference statements)
5
151
0
12
Order By: Relevance
“…273 Another site of interest in the treatment of aggressive behavior has been the posterior hypothalamic region (pHr), a region that shows strong interconnection with the amygdalae. 245 As in the amygdala, lesions in the pHr have been used for the combination of epilepsy and aggressive behavior. 244,255 Modern application of DBS to the pHr has mostly been for cases of mental retardation combined with severe aggression, and thus few results have been reported.…”
Section: Aggressive Behaviormentioning
confidence: 99%
“…273 Another site of interest in the treatment of aggressive behavior has been the posterior hypothalamic region (pHr), a region that shows strong interconnection with the amygdalae. 245 As in the amygdala, lesions in the pHr have been used for the combination of epilepsy and aggressive behavior. 244,255 Modern application of DBS to the pHr has mostly been for cases of mental retardation combined with severe aggression, and thus few results have been reported.…”
Section: Aggressive Behaviormentioning
confidence: 99%
“…Within the "panic circuit" (Gorman et al, 2000;Shekhar et al, 2002), the hypothalamus plays a key role in initiating panic-like responses (Sano et al, 1970;Abelson and Curtis, 1996;Schreiber et al, 1996;Javanmard et al, 1999;Lipp et al, 2005). The dorsomedial hypothalamus (DMH) plays an important role coordinating the neuroendocrine, autonomic, and behavioral responses to emotional stress Chou et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Sano's explanation for the different outcomes was that surgery on lower-order areas produces more marked and lasting clinical effects than surgery on higher-order areas, because the overlapping of the ergotropic circuit with other circuits is more marked in the neocortex than the allocortex and in the allocortex than the diencephalon. 52 Sano et al [52][53][54][55] reported the most detailed and consistent surgical series concerning patients with aggressive behavior treated by radiofrequency lesioning of the pHyp. Also worth mentioning is that other teams at that time proposed pHyp lesioning for the treatment of aggressive behavior.…”
Section: Human Surgery: the Lesional Era And Neurophysiological Testingmentioning
confidence: 99%
“…They developed a functional atlas of hypothalamic responses to stimulation using the Schaltenbrand-Bailey atlas. Following these considerations, Sano et al 54 developed the concept of the "ergotropic triangle," in which sympathetic activity was elicited through intraoperative high-frequency stimulation, which became a sign of correct electrode placement. It is not clear if the stimulation covered the pHyp, the dorsal longitudinal fasciculus that arises there, or both.…”
Section: Human Surgery: the Lesional Era And Neurophysiological Testingmentioning
confidence: 99%